ALAT PENGERING TANPA LISTRIK MENGGUNAKAN SUNLIGHT COLLECTOR TECHNOLOGY OPTIMALISASI PRODUKSI LENTENG - W, Candra Restu; Yuliyani, Yuliyani; Y, Nur Ivan; Z, Fauzi Firdha (Universitas Muhammadiyah Magelang, 2018)
Lenteng is a food made from flaked cassava batter and then fried. In terms of the shape of the lent has similarities with cassava opak. The application of technology in the production process is still minimal and the limited capital to buy equipment makes the development of UMKM business owned by Mrs. Sudiyati still tend to stagnant. The main problem in the production of Lenteng is the time of drying of the Lenteng which reaches 2 days with traditional drying. The purpose of this research is to make Lenteng dryers that do not use electricity as energy source and design an effective and efficient tool so that it can speed up the drying process to increase the production amount. The output target of this research is the Electric less Dry using Sunlight Collector Technology and being innovative in helping to accelerate the drying process of the Lenteng. The method used in this research is literature study, survey, design or drawing design, dryer manufacture, field testing and analysis, tool evaluation, and preparation of final report of PKM activities. From the data of dry material test results can be seen that the weight of the product before and after dried in APTL has a difference of 4-11 grams so the result is drier, whereas from the temperature test results data can be seen that the temperature in APTL higher 7-19,1oC which can affect the drying process significantly. Based on these calculations APTL (Dryer Without Electricity can increase production of 4.67 kg of Lenteng from initial production and drying process with increasing temperature up to 69.9 ° C and 10% humidity can dry the lent in 2-3 hours or 4,67- 7X faster than traditional drying, and using APTL can save the drying place, which required 12 rigs to dry 20 kg of lent, with this Dryer only requires 5 dryers with a capacity of 3.752 kg per drying whereas Rigen (traditional) only loading 1, 675 kg per drying